Peran Sains dan Teknologi dalam Meningkatkan Intelektual Kader HMI Berkualitas Insan Cita - Ikbal Setiawan (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2020)
This research aim to know: (1) the role of science and technology is utilized to improve the intellectuals of HMI cadres in the Banjarbaru Branch, (2) The quality of the role of science and technology in improving the intellectuals of HMI cadres in the Banjarbaru branch. The benefits of this research can be as an insight enhancer and as motivation for HMI cadres in carrying out missions and can be an example of the importance of deepening knowledge and increasing skills. This research method uses descriptive research with a quantitative approach. The purpose of using this method is to uncover facts, parse phenomena, and produce quantitative data. The subjects of this study consisted of 7 (seven) cadres of HMI Banjarbaru Branch. These findings indicate 2 basic findings. First, science and technology have an important role in enhancing the intellectuals of HMI cadres. Second, the role of science and technology is able to improve the quality of human minds in HMI cadres as provisions for carrying out missions. It is also hoped that by having a lot of provisions, an HMI cadre can become an initiator in implementing his knowledge and skills in order to benefit society.